The Journal of Ecclesiastical History (Cambridge)
The Journal of Ecclesiastical History has published original research articles, scholarly reviews, review articles, notes and documents, relating to all aspects of the history of Christianity. The journal's scope extends to cultural, institutional, intellectual, political, social and any other relevant form of history; to all periods from ancient to modern; and to all regions of the world. Contributors address detailed research questions as well as engaging with the wider issues in the field.
Keywords: Church History